Implementing the Virtual Project Management Office: Proven Strategies for Success - Goncalves Marcus (MC Graw Hill, 2007)
Globalization and increased outsourcing have redefined project management. The complex dynamics involved in today's long-distance projects require a new skill set and knowledge base unlike anything needed before.